Preoperative smoking cessation interventions: a systematic review and meta-analysis - Mohammed Alsanad; Mohammed Aljanoubi; Faraj K. Alenezi; Amanda Farley; Babu Naidu; Joyce Yeung (Perioperative Medicine)
Abstract Background Smoking is the leading single cause of preventable death in England and also increases the risk of postoperative complications. The preoperative period is a potential opportunity to introduce smoking cessation interventions to smokers to reduce the risk of postoperative complications. A systematic search was conducted to find all studies that investigated the effectiveness of preoperative smoking cessation interventions. The primary outcome was smoking cessation at surgical time to the last follow-up, and the secondary outcome was postoperative complications that required treatment or ICU admission. A random-effects meta-analysis was used to synthesize the outcomes. Sixteen studies were included in the review (3505 participants), and 14 studies were included in the meta-analysis (2940 randomized participants). The quality of evidence was moderate due to the high risk of bias and heterogeneity. We found that patients who were provided with a smoking cessation intervention had significantly increased odds of quitting smoking by the time of surgery compared with usual care, with a reported relative risk (95% CI) 1.64 (1.30–2.07) and at the longest follow-ups with RR (95% CI) 1.38 (1.12–1.70). Moreover, there was no difference found in the rate of postoperative complications between intervention and control conditions with RR (95% CI) 0.81 (0.62–1.06). The use of standardized outcome measurements is recommended to reduce heterogeneity for future studies, and further investigation focusing on patient perspectives is needed. Trial registration PROSPERO CRD42023423202.